PENERAPAN PENDEKATAN PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SDN 22 SUNGAI PAKNING - Widawahyuni, Sri; ', Syahrilfuddin; ', Lazim. N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrak: The problems that occurred in the class V students of SDN 22 Sungai Pakning is the low learning result in science subject first half. This is evident from data on the number of students who completed 5 votes (27,78%) and not completed 13 votes (72,22) with an average of 57,94. As this study aims to improve learning outcomes class V science students at SDN 22 Sungai Pakning by applying learning approach contextual teaching and learning (CTL). The defense approuch contextual teaching and learning (CTL) is to connect learning with real life students themselves, so that students are able to understand the material being studied. The research was conducted at SDN 22 Sungai Pakning in class V students the second semester of the school year. In the total number of students of class V are 18 people consisting of 8 women and 10 men. Research is classroom action research (PTK) is carried out with 2 cycle, meeting four times and twice daily tests using learning tools. An increase in activity of teachers and students each cycle using the application approach contextual teaching and learning (CTL). In daily test cycle 1 the average value yes 67,22 to finish with 12 students (66,67%) and is not finished 6 students (33,33%), while in the daily quiz 2 cycle 2 average value completeness 74,16 with 16 students (88,89) and finished 2 students (11,11%) Key words : Contextual Teaching And Learning (CTL) Approuch, learning result of science